Service Systems in the Era of the Internet of Things: A Smart Service System Taxonomy - Brogt, Tobias; Strobel, Gero (Proceedings of the 28th European Conference on Information Systems (ECIS), 2020)
Services are becoming increasingly important, and service systems are seeing the use of service-dominant logic to understand value creation through the integration of active and passive resources. Digital transformation is significantly influencing service systems, and new, smart technologies are enabling innovative value propositions, leading to smart service systems. Smart products, which are a part of the Internet of Things, are the main building blocks of such systems. Attempts have been made to conceptualize smart service systems, but there seems to be no consensus in the literature because, for example, smart products have not been defined in a consistent way. We therefore examine ways to classify smart service systems in terms of their characteristics and attributes. We develop a taxonomy based on a systematic literature review focusing on smart features. Furthermore, an evaluation using domain-specific use cases demonstrates the applicability of the taxonomy. Our contribution combines and extends the available conceptualizations regarding smart service systems to pave the way for the necessary future research.
Keywords: Smart Service System; Taxonomy; Internet of Things; Smart Products